Awakening Environmental Responsibility in Youth Through Islamic Values in Green Governance Education - Andriana, Isni; Zamroni, M. Afif; Thamrin, Kemas M Husni; Kalsum, Umi; Fuadah, Luk Luk; Rifanka, Namira Salsa; Khalisah Chaidir, Kiara Shafah; Usman, Fadly (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2025)
This study investigates how Islamic values can foster environmental responsibility and influence youth behavior within the context of green governance education. Despite the expansion of global and national environmental policies, their effectiveness is often limited by weak ethical engagement and a lack of value-based education at the grassroots level. Existing research typically focuses on policy frameworks or institutional reforms, neglecting the potential of faith-based education to transform student awareness. To address this gap, the present study employs a qualitative case study design rooted in Social Justice Theory in Islam (Choudhury, 2020), which views humans as khalifah (stewards) responsible for upholding adl (justice) and tawazun (balance) in all aspects of life. Data were gathered through three Focus Group Discussions (FGDs) with 28 university students from South Sumatra, Indonesia, representing two universities that actively participate in the UI GreenMetric program. Thematic analysis revealed that students' comprehension of Islamic environmental ethics transcended mere conceptual understanding, translating into responsible consumption, community engagement, and peer-led sustainability initiatives. These findings demonstrate that participatory Islamic pedagogy can cultivate moral leadership and ecological consciousness, positioning students as active advocates for environmental justice. The novelty of this study lies in its comprehensive analysis of how Islamic ethical principles are applied within green governance education, an area seldom explored in higher education. The results emphasize the need for Islamic education policy to incorporate faith-based environmental ethics into curricula, promoting spiritually grounded and sustainability-oriented youth leadership.